Olfactory Dysfunction in Neurodevelopmental Disorders: A Meta-Analytic Review of Autism Spectrum Disorders, Attention Deficit/Hyperactivity Disorder and Obsessive-Compulsive Disorder - Crow, Andrew J. D. (J Autism Dev Disord, 2020)
Olfactory dysfunction is recognized in neurodevelopmental disorders and may serve as an early indicator of global dysfunction. The present meta-analysis measures olfaction effect sizes in attention-deficit/hyperactivity disorder (ADHD), autism spectrum disorders (ASD), and obsessive-compulsive disorder (OCD). Meta-analysis included 320 ADHD, 346 ASD, and 208 OCD individuals as compared to 910 controls. Olfactory performance deficits were small-to-moderate and heterogeneous (d = −0.42, 95% CI = −0.59 < δ < −0.25). Meta-analytic results indicate that olfactory dysfunction is evident in individuals with ASD and OCD, with small-to-negligible effects in ADHD. These findings imply olfactory dysfunction is related to clinical phenotype in ASD and OCD, but not ADHD, and warrant inclusion in clinical assessment and evaluation of certain neurodevelopmental disorders.